트레드밀 운동이 뇌졸중 환자의 폐기능과 보행능력에 미치는 효과 : 메타분석 - 조성현; 최기복; Cho, Sunghyoun; Choi, Kibok (Journal of the Korean Society of Integrative Medicine, 2020)
Purpose : This study aimed to conduct a comprehensive meta-analysis to evaluate the effect size for pulmonary function and gait capacity of treadmill exercise in stroke patients. In addition, we aimed to examine the current status of treadmill interventions and compare the effect sizes of treadmill training to provide evidence-based practice for future development and application. Methods : The meta-analysis study was conducted using research articles that applied treadmill exercise to stroke patients and were published between January 2005 and February 2020. For a systematic meta-analysis, we conducted a search using the PICOS framework and selected 25 domestic stroke- and treadmill-related studies. The Comprehensive Meta-Analysis program was used to calculate the effect sizes for lung function and gait capacity (6-minute walk test and 10 m walk test). As Cohen's d has a tendency to overestimate the effect size, we used Hedge's g to increase the accuracy in computing the effect size. Results : Based on the results of the meta-analysis, the total effect size of treadmill exercise was 0.535, which was statistically significant, with a medium effect size (p<0.05). The effects of treadmill exercise in stroke patients were divided into dependent variables, namely pulmonary function (0.372) and gait capacity (0.584). In addition, for gait capacity, the effect sizes were evaluated for both the 6-minute walk test (0.756) and the 10 m walk test (0.514). Conclusion : This study provides objective evidence of the effectiveness of treadmill-based gait training programs. We hope that the results of this study will help support the development and implementation of treadmill-based gait training in stroke patients. Treadmill training is expected to improve not only pulmonary function, but also the gait capacity of stroke patients. Long-term investigations on the effects of treadmill training in stroke patients are necessary.